An analysis of 2‐day cardiopulmonary exercise testing to assess unexplained fatigue. Issue 17 (5th September 2020) - Lindheimer, Jacob B.; Alexander, Thomas; Qian, Wei; Klein‐Adams, Jacquelyn C.; Lange, Gudrun; H. Natelson, Benjamin; Cook, Dane B.; Hill, Helene Z.; Falvo, Michael J.
Abstract: Two consecutive maximal cardiopulmonary exercise tests (CPETs) performed 24 hr apart (2‐day CPET protocol) are increasingly used to evaluate post‐exertional malaise (PEM) and related disability among individuals with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). This protocol may extend to other fatiguing illnesses with similar characteristics to ME/CFS; however, 2‐day CPET protocol reliability and minimum change required to be considered clinically meaningful (i.e., exceeding the standard error of the measure) are not well characterized. To address this gap, we evaluated the 2‐day CPET protocol in Gulf War Illness (GWI) by quantifying repeatability of seven CPET parameters, establishing their thresholds of clinically significant change, and determining whether changes differed between veterans with GWI and controls. Excluding those not attaining peak effort criteria ( n  = 15), we calculated intraclass correlation coefficients (ICCs), the smallest real difference (SRD%), and repeated measures analysis of variance (RM‐ANOVA) at the ventilatory anaerobic threshold (VAT) and peak exercise in 15 veterans with GWI and eight controls. ICC values at peak ranged from moderate to excellent for veterans with GWI (mean [range]; 0.84 [0.65 – 0.92]) and were reduced at the VAT (0.68 [0.37 – 0.78]). Across CPET variables, the SRD% at peak exercise for veterans with GWI (18.8 [8.8 – 28.8]) was generally lower than at the VAT (28.1 [9.5 – 34.8]). RM‐ANOVAs did not detect any significant group‐by‐time interactions (all p  > .05). The methods and findings reported here provide a framework for evaluating 2‐day CPET reliability, and reinforce the importance of carefully considering measurement error in the population of interest when interpreting findings. Abstract : Two consecutive maximal cardiopulmonary exercise tests (CPETs) performed 24 hr apart (referred to as 2‐day CPET protocol) are increasingly promoted as an important clinical tool for illness diagnosis and measurement of disability in conditions with idiopathic fatigue; however, reliability and minimum values necessary to be considered clinically meaningful are not well characterized. With an emphasis on taking standard error of the measure into account, this study introduces a framework for evaluating repeatability and establishing reference values in the 2‐day CPET.